Pelatihan MPKP untuk Meningkatkan Pengetahuan Perawat tentang MPKP di RSJ Grhasia Yogyakarta - Hadi Pramono; S Sudiharja; Unang Suryana (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
The professional nursing practice model (MPKP) is one of the efforts to improve the quality of nursing services. Knowledge is one of the important factors to support the optimal implementation of MPKP. The purpose of this study was to increase nurses' knowledge about MPKP and the implementation of MPKP in Grhasia Hospital through MPKP training. This research is a quantitative research with a pre-experimental design. The approach used is one group pretest and posttest design. Respondents in this study were all 37 Grhasia Hospital nurses who attended MPKP training. the average knowledge of nurses about MPKP before the training was 71.62, then after the MPKP training the average knowledge of nurses became 128.11. The results of the normality test showed that there was an abnormal distribution of the data so that the bivariate analysis used the Wilcoxon test. Based on the results of the Wilcoxon test, a p-value of 0.000 was obtained, so it can be concluded that MPKP training can increase nurses' knowledge about MPKP. Researchers consider it necessary to do further research on the implementation of MPKP in Grhasia Hospital Yogyakarta.